TINDAK TUTUR KOMUNIKASI DALAM PELAYANAN MASYARAKAT DI MASYARAKAT PEDULI LINGKUNGAN (MPL) SAWAH SUDUT NAGARI SALAYO KECAMATAN KUBUNG KABUPATEN SOLOK - Andi Marta, Redo; Halid, Elan; Rahayu, Zona Rida; Putri, Mega; Wirasty. B, Rini; Dwinita, Suci; Adhia, Hana; Ikhwan, Ikhwan; Zaimil, Roza; Roza, Helvita; Dwiputri, Risza; Zora, Fera (PUAN INDONESIA, 2025)
The Environmental Care Community (MPL) in Nagari Selayo, Kubung District, Solok Regency, is committed to realizing excellent service to the community through communication speech acts in serving the community. In this effort, the Environmental Care Community (MPL) educates the community about the importance of providing services to the community using good communication speech acts in dealing or carrying out activities. In communicating, the community needs to use three magic words, namely apologizing, asking for help, and saying thank you in carrying out activities at this institution. With a collaborative approach, the Environmental Care Community (MPL) also holds seminars and workshops that aim to increase public awareness when dealing or carrying out activities at this institution. Through this activity, it is hoped that the community and the Environmental Care Community (MPL) institution can understand the responsibility in maintaining good and correct speech or communication so that serving or dealing runs smoothly.